Relationship between HLA-DRB1 shared epitope alleles and peripheral blood monocyte counts in Japanese patients with rheumatoid arthritis - Daisuke Hiraoka; Jun Ishizaki; Kenta Horie; Kensuke Oryoji; Shin-ichi Mizuki; Katsuto Takenaka (PLoS ONE, 2025)
Objectives To investigate the relationship between Human Leukocyte Antigen-DR beta 1 (HLA-DRB1) shared epitope (SE) alleles and peripheral blood monocyte counts in disease-modifying antirheumatic drug-naïve patients with rheumatoid arthritis (RA), and also the relationship between specific SE alleles and anti-cyclic citrullinated peptide antibody (anti-CCP Ab) titers. Methods This retrospective single-center study included 86 Japanese patients with RA. HLA-DRB1 genotyping was performed, and SE alleles associated with a high risk of developing RA were classified into the S 2 (*04:01) and S 3P (*01:01, *01:02, *04:04, *04:05, *04:08, and *10:01) categories. Patients were stratified based on monocyte count tertiles. The relationships between monocyte counts at diagnosis and clinical, serological, and genetic factors were analyzed. Logistic regression was used to identify independent factors associated with high monocyte counts. Results SE-positive patients, particularly those with S 3P alleles, had significantly higher monocyte counts than SE-negative patients. A multivariate analysis revealed that male sex and S 3P positivity, particularly HLA-DRB1 *01:01 or *04:05, were independently associated with higher monocyte counts. Patients carrying at least one S 3P allele had significantly higher anti-CCP Ab titers, with patients homozygous for HLA-DRB1 *04:05 having the highest levels. A similar relationship was not found with HLA-DRB1 *01:01 despite its strong effect on monocyte counts. Conclusions This is the first study to demonstrate a significant association between SE alleles and peripheral blood monocyte counts in RA. The results obtained suggest that specific SE alleles, particularly S 3P alleles, contribute to the early pathogenesis of RA by enhancing monocyte-driven immune activation and anti-CCP Ab production.